Effects of retrogressive permafrost thaw slumping on benthic macrophyte and invertebrate communities of upland tundra lakes - Mesquita, Patricia S. (2008)
Global warming is forecast to cause significant thawing of the permafrost that surrounds lakes and rivers across the Arctic, with potential wide-scale effects on the water quality and biotic characteristics of these water bodies. The benthic environment is believed to be especially sensitive to permafrost-induced ecological change, and this has been the focus of recent field intensive research. Five lakes disturbed and three lakes undisturbed by retrogressive permafrost thaw slumps were sampled during late summer of 2006 to assess the potential effects of slumping on benthos. Water quality parameters, submerged macrophytes, benthic invertebrates, and sediment were collected. A significant difference (p < 0.05) between disturbed and undisturbed lakes was found for macrophyte, invertebrates, underwater light attenuation, and some sediment variables. The results suggest that thaw slumps can affect submerged macrophyte biomass, benthic invertebrate abundance, and also community structure in upland tundra lakes. Such differences between undisturbed and disturbed lakes are suggested to be related to changes in water column transparency, sediment nutrient availability, soil and terrestrial vegetation loading from the landscape, and changes in slope angle of the littoral zone.